2018
DOI: 10.1177/1359105318785450
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation in non-depressed individuals: The effects of a chronic, misunderstood illness

Abstract: Chronic illness is a risk factor for suicide but is often explained with depression. Research has shown an increased suicide rate in patients with myalgic encephalomyelitis and chronic fatigue syndrome, but specific risk factors have been unexplored. We qualitatively analyzed responses from 29 patients who endorsed suicidal ideation but did not meet depression criteria. Two themes were developed: (1) feeling trapped and (2) loss of self, loss of others, stigma and conflict. Myalgic encephalomyelitis and chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…Indeed, previous research has found these circumstances are risk factors for suicidal ideation in this population. 21…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous research has found these circumstances are risk factors for suicidal ideation in this population. 21…”
Section: Discussionmentioning
confidence: 99%
“…See Table 1 for a list of risk factors and their classification. Factors marked with an asterisk are especially relevant to ME/CFS patients, based on one study in Spain [6] and another in the United States [17]. Demographic and historical characteristics [12,18] are often chronic and not modifiable.…”
Section: Risk Factors For Suicidementioning
confidence: 99%
“…Maria's marital status, solo living situation, poor financial state, and lack of consistent social contact (whether via family, friends, or work) also place her at higher risk. In the United States, among non-depressed patients with ME/CFS, lack of resources, including social/financial support and occupational engagement, was the most cited reason (by 79%) contributing to suicidal ideation [17]. Among Spanish patients, lack of resources was linked to suicidal ideation, depression, and hopelessness [6].…”
Section: Risk Factors For Suicidementioning
confidence: 99%
See 1 more Smart Citation
“…6 Addressing such concerns will not only prevent the common problems such as burn out, undue anxiety, fear, depression, but can also decrease the rate of suicide, drug dependence and addiction among the young doctors. 7 The rationale of this study is to investigate the prevalence of stress, anxiety and depression and its relation with chronic fatigue among medical students of CMH Lahore Medical College, taking gender differences into account. Two questionnaires were used for this study.…”
Section: Introductionmentioning
confidence: 99%